Family Caregiver Support Program to Increase Quality Care Among the Geriatric Population - Elizabeth Yun Yun Vinsur; Febrina Secsaria Handini; Anang Nurwiyono (STIKep PPNI Jawa Barat, 2023)
Aims: This study aimed to determine the effect of providing support programs to family caregivers on the quality of care for the elderly with chronic diseases in Pandansari Village, Poncokusumo District, Malang Regency. Methods: The study used a pre-experimental with one group pretest-posttest research design approach in 7 weeks from July-September 2022. The total sample size was 50 respondents using purposive sampling technique. The selected sample must fulfill criteria’s, includes: 1) an informal caregiver who lives with the elderly, 2) takes care of the elderly with chronic diseases, and 3) not suffering from chronic diseases itself. The WHO-QOL BREF questionnaire was used to collect data on the quality of life before and after the provision of support programs. Analysis includes univariate and bivariate. Bivariate using the Wilcoxon test. Results: In this study, the caregivers are all women (100%) and most of the elderly are women (60.0%), the chronic diseases are Hypertension 66% and Gout Arthritis 34%. The results of this study indicate a significant effect of providing family caregiver support programs on the quality of care for the elderly with chronic diseases based on the quality of life indicators (p: 0.0001). Conclusion: Family support programs influence the quality of care in terms of improving the quality of life of the elderly. Discussion: In caring for the elderly with chronic diseases, family caregivers can take advantage of family support programs. Furthermore, this research is expected to provide insights and ideas for further research especially the development of support programs for caregivers of families with other chronic diseases.